2022
DOI: 10.1007/s00170-022-10276-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of groove configuration on mechanical properties and fracture behavior of 6061 Al alloy and CFRTP laser joint

Abstract: Laser surface texturing is generally a promising approach to enhance the adhesion property of metalthermoplastic hybrid structure, and the effect is related to the groove con guration. Laser joining of carbon ber reinforced thermoplastic composite (CFRTP) to 6061 Al alloy under various groove con guration was carried out, aimed to investigate the effect of groove width and depth on interfacial morphology, mechanical properties and fracture behavior of CFRTP/ Al joints. The tensile-shear force was tested, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The results showed that the higher the surface roughness of aluminum alloy, the better the wettability of molten GFRTP and the stronger the joint mechanical properties. Liu et al [42] studied the effect of groove width and groove depth on the joint strength of Al/CFRTP. The results show that the tensile-shear strength of CFRTP/Al joints first increases and then decreases with the increase in groove width and groove depth.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the higher the surface roughness of aluminum alloy, the better the wettability of molten GFRTP and the stronger the joint mechanical properties. Liu et al [42] studied the effect of groove width and groove depth on the joint strength of Al/CFRTP. The results show that the tensile-shear strength of CFRTP/Al joints first increases and then decreases with the increase in groove width and groove depth.…”
Section: Introductionmentioning
confidence: 99%
“…Laser grooves or patterns that affect material surface properties, such as adhesiveness, friction coefficient, wettability, and appearance [1][2][3][4], have many attractive applications. Lasers with short pulses in nanosecond range have been widely used for creating surface micro-patterns.…”
Section: Introductionmentioning
confidence: 99%